Visual Sensory Deprivation (VSD): An Innovative Training Method for Proprioceptive Specific-Strength Enhancement - Tam, T. (Track Coach, 2021)
Though the author describes how Visual Sensory Deprivation exercises may be incorporated into hammer throw training he makes it clear that VSD may be beneficial for any discipline requiring balance, precision, power, strength and conditioning. Sports science research has significantly contributed over the years in improving Paralympic performances. Various studies have demonstrated that the physical preparation of visually impaired athletes competing in Paralympics events incorporates similar strength/power exercises as their sighted counterparts. However, intricate physiological distinctions do exist between visually-impaired Paralympians and Olympic athletes within a training framework. The components associated with the former include altered postural stability, non-visual proprioception and modified somatosensory systems. A greater understanding of these components can therefore potentially create an innovative training scheme for non-visually impaired competitors. The rationale of this paper is to propose a way to enhance proprioceptive specificstrength using a Visual Sensory Deprivation (VSD) method catered for elite sighted athletes. This article will use the hammer-throw in track & field to demonstrate the application of such a VSD protocol.